Molecular sieve SSZ-120, its synthesis and use

JP7634562B2Active Publication Date: 2025-02-21CHEVRON USA INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022571136
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-22
Filing Date
2021-05-18
Publication Date
2025-02-21
Estimated Expiration
2041-05-18

Smart Images

  • Figure 0007634562000024
    Figure 0007634562000024
  • Figure 0007634562000025
    Figure 0007634562000025
  • Figure 0007634562000026
    Figure 0007634562000026
Patent Text Reader

Abstract

Aluminogermanosilicate molecular sieve material, designated SSZ-120, with small crystal size and high surface area is provided. SSZ-120 can be synthesized using 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication as a structure-directing agent. SSZ-120 can be used in organic compound conversion reactions and / or sorption processes.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Application No. 63 / 028,642, filed May 22, 2020.

[0002] Field This disclosure relates to a small crystal size, high surface area aluminogermanosilicate molecular sieve designated SSZ-120, its synthesis, and its use in organic compound conversion reactions and sorption processes. [Background technology]

[0003] background Molecular sieves are a commercially important class of materials having a well-defined crystal structure with a defined pore structure as revealed by distinct X-ray diffraction (XRD) patterns and specific chemical compositions. The crystal structure defines the cavities and pores that are characteristic of the particular type of molecular sieve.

[0004] According to the present disclosure, a small crystal size, high surface area aluminogermanosilicate molecular sieve, designated SSZ-120, with a unique powder X-ray diffraction pattern was synthesized using 3,3′-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication as a structure directing agent. Summary of the Invention

[0005] summary In a first aspect, there is provided an aluminogermanosilicate molecular sieve which, in calcined form, has an X-ray powder diffraction pattern including the peaks in the following table: [Table 4]

[0006] Calcined molecular sieves are at least 500m 2 / g total surface area (as determined by the nitrogen physisorption t-plot method) and / or at least 100 m 2 / g of external surface area (as determined by nitrogen physisorption t-plot method).

[0007] In a second aspect, there is provided an aluminogermanosilicate molecular sieve having, in as-synthesized form, an X-ray powder diffraction pattern including the peaks in the following table: [Table 3]

[0008] In the as-synthesized anhydrous form, the aluminogermanosilicate molecular sieve may have a chemical composition including the following molar relationships: [Table 2] wherein Q comprises a 3,3′-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication.

[0009] In a third aspect, there is provided a method for synthesizing an aluminogermanosilicate molecular sieve, the method comprising: (1) providing a reaction mixture comprising: (a) an FAU framework-type zeolite; (b) a germanium source; (c) a structure directing agent (Q) comprising 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication; (d) a fluoride ion source; and (e) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the aluminogermanosilicate molecular sieve.

[0010] In a fourth aspect, there is provided a process for converting a feedstock comprising an organic compound to a conversion product, the process comprising contacting the feedstock under organic compound conversion conditions with a catalyst comprising an activated form of an aluminogermanosilicate molecular sieve as described herein.

[0011] In a fifth aspect, there is provided an organic nitrogen compound comprising a dication having the following structure: [ka] In relation to the present invention, the following is further disclosed: [1] An aluminogermanosilicate molecular sieve having, in calcined form, an X-ray powder diffraction pattern including the peaks in the following table: [Table 4] [2] The molecular sieve has a molecular sieve adsorption capacity of at least 500 m as measured by the nitrogen physisorption t-plot method. 2 / g total surface area and / or nitrogen physisorption of at least 100 m as measured by the t-plot method 2 The aluminogermanosilicate molecular sieve according to [1], comprising crystals having an external surface area in the range of 100 / g. [3] The total surface area is 500 to 800 m 2 / g range of the aluminogermanosilicate molecular sieve according to [2]. [4] The outer surface area is 100~300m 2 / g range of the aluminogermanosilicate molecular sieve according to [2]. [5] The molar relationships are as follows: Al 2 O 3 :(n)(SiO 2 +GeO 2 ) The aluminogermanosilicate molecular sieve according to [1], having a composition represented by the formula: [6] An aluminogermanosilicate molecular sieve which, in its as-synthesized form, has a powder X-ray diffraction pattern including the peaks in the table below. [Table 3] [7] It has the following composition in molar ratio: [Table 2A] The aluminogermanosilicate molecular sieve according to [6], wherein Q comprises 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication. [8] It has a chemical composition having the following molar relationship: [Table 2B] The aluminogermanosilicate molecular sieve according to [6], wherein Q comprises 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication. [9] 1. A method for synthesizing an aluminogermanosilicate molecular sieve, said method comprising: (1) (a) FAU framework zeolite; (b) a germanium source; (c) structure-directing agent (Q) containing 3,3′-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication; (d) a source of fluoride ions; and (e) providing a reaction mixture comprising water; (2) subjecting said reaction mixture to crystallization conditions sufficient to form crystals of said aluminogermanosilicate molecular sieve.

[10] The method according to [9], wherein the reaction mixture has the following composition in molar ratio: [Table 1A]

[11] The method according to [9], wherein the reaction mixture has the following composition in molar ratio: [Table 1B]

[12] The method according to [9], wherein the FAU framework type zeolite is zeolite Y.

[13] The method according to [9], wherein the crystallization conditions include heating the reaction mixture under autogenous pressure at a temperature between 100° C. and 200° C. for 1 day to 14 days.

[14] A process for converting a feedstock containing an organic compound to a conversion product, the process comprising contacting the feedstock with a catalyst comprising the aluminogermanosilicate molecular sieve of [1] under organic compound conversion conditions.

[15] An organic nitrogen compound containing a dication having the structure: [ka] [Brief description of the drawings]

[0012] Brief description of the drawings [Figure 1]1 shows the powder X-ray diffraction (XRD) pattern of the as-synthesized product of Example 2.

[0013] [Figure 2(A)] 1 shows scanning electron microscope (SEM) images of the as-synthesized product of Example 2 at different magnifications. [Figure 2(B)] 1 shows scanning electron microscope (SEM) images of the as-synthesized product of Example 2 at different magnifications. [Figure 2(C)] 1 shows scanning electron microscope (SEM) images of the as-synthesized product of Example 2 at different magnifications. [Figure 2(D)] 1 shows scanning electron microscope (SEM) images of the as-synthesized product of Example 2 at different magnifications.

[0014] [Diagram 3] 1 shows a powder XRD pattern of the calcined product of Example 3.

[0015] [Figure 4] 1 is a graph showing the relationship between conversion or yield and temperature for the hydroconversion of n-decane over a Pd / SSZ-120 catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Detailed Description definition The term "framework type" has the meaning set forth in the "Atlas of Zeolite Framework Types", by Ch. Baerlocher and LB McCusker and DH Olsen (Sixth Revised Edition, Elsevier, 2007).

[0017] The term "zeolite" refers to an aluminosilicate molecular sieve having a framework constructed from alumina and silica (ie, repeating AlO4 and SiO4 tetrahedral units).

[0018] The term "aluminogermanosilicate" refers to a molecular sieve having a framework built of AlO4, GeO4, and SiO4 tetrahedral units. The aluminogermanosilicate may contain only the specified oxides, in which case it may be described as a "pure aluminogermanosilicate," or it may contain other additional oxides as well.

[0019] The term "as-synthesized" is used herein to refer to the molecular sieve in the form after crystallization and prior to removal of the structure directing agent.

[0020] The term "anhydrous" is used herein to refer to a molecular sieve that is substantially devoid of both physically and chemically adsorbed water.

[0021] The term "SiO2 / Al2O3 molar ratio" may be abbreviated as "SAR."

[0022] Molecular sieve synthesis The aluminogermanosilicate molecular sieve SSZ-120 can be synthesized by: (1) providing a reaction mixture comprising (a) an FAU framework-type zeolite; (b) a germanium source; (c) a structure directing agent (Q) comprising 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication; (d) a fluoride ion source; and (e) water; (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the aluminogermanosilicate molecular sieve.

[0023] The reaction mixture may have a composition, in terms of molar ratios, within the ranges set forth in Table 1. [Table 1] wherein Q comprises a 3,3′-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication.

[0024] In some embodiments, the reaction mixture can have a SiO2 / GeO2 molar ratio in the range of 4 to 12 (e.g., 6 to 10).

[0025] The FAU framework type zeolite can be an ammonium type zeolite or a hydrogen type zeolite (e.g., NH4 type zeolite Y, H type zeolite Y). The FAU framework type zeolite can be zeolite Y (e.g., CBV720, CBV760, CBV780, HSZ-385HUA, and HSZ-390HUA). Preferably, the FAU framework type zeolite is zeolite Y. More preferably, the zeolite Y has a SiO2 / Al2O3 molar ratio in the range of about 30 to about 500. The FAU framework type zeolite can include two or more zeolites. Usually, the two or more zeolites are Y zeolites having different SiO2 / Al2O3 molar ratios. The FAU framework type zeolite can also be the only silica and aluminum source for forming the aluminogermanosilicate molecular sieve.

[0026] Germanium sources include germanium oxide and germanium alkoxides (eg, germanium ethoxide).

[0027] Fluoride ion sources include hydrogen fluoride, ammonium fluoride, and ammonium difluoride.

[0028] SSZ-120 can be synthesized using a structure directing agent (Q) comprising 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication, represented by the following structure (1): [ka]

[0029] Suitable sources of Q are the hydroxide, chloride, bromide, and / or other salts of diquaternary ammonium compounds.

[0030] The reaction mixture may include seed crystals of a molecular sieve material, such as SSZ-120, from a previous synthesis in an amount of 0.01 to 10,000 ppm (e.g., 100 to 5000 ppm) by weight of the reaction mixture. Seeding may be advantageous in improving the selectivity of SSZ-120 and / or shortening the crystallization process.

[0031] It should be noted that the reaction mixture components can be supplied from multiple sources, or two or more reaction components can be provided by a single source. The reaction mixture can be prepared in either a batch or continuous manner.

[0032] Crystallization and post-synthesis treatment Crystallization of the molecular sieves from the above reaction mixture can be carried out under either static, rotating, or stirred conditions in a suitable reaction vessel, such as a polypropylene jar, or a Teflon-lined or stainless steel autoclave, placed in a convection oven maintained at a temperature of 100° C. to 200° C. for a sufficient time for crystallization to occur at the temperature used (e.g., 1 day to 14 days). Hydrothermal crystallization processes are usually carried out under autogenous pressure.

[0033] Once the desired molecular sieve crystals have formed, the solid product is separated from the reaction mixture by standard separation techniques such as filtration or centrifugation. The collected crystals are washed with water and dried for a few seconds to a few minutes (e.g., 5 seconds to 10 minutes for flash drying) or for a few hours (e.g., 4 hours to 24 hours for oven drying at 75 °C to 150 °C) to obtain as-synthesized SSZ-120 crystals with at least a portion of the structure directing agent within the pores. The drying step can be carried out at atmospheric pressure or under vacuum.

[0034] The as-synthesized molecular sieve may be subjected to heat treatment, ozone treatment, or other treatment to remove some or all of the structure directing agent used in its synthesis. Removal of the structure directing agent may be accomplished by heat treatment (i.e., calcination) in which the as-synthesized molecular sieve is heated in air or in an inert gas at a temperature sufficient to remove some or all of the structure directing agent. Pressures less than atmospheric may be used for the heat treatment, but atmospheric pressure is preferred for convenience. The heat treatment may be performed at a temperature of at least 370° C. for at least 1 minute and generally up to 20 hours (e.g., 1 to 12 hours). The heat treatment may be performed at a temperature of up to 925° C. For example, the heat treatment may be performed in air at a temperature of 400° C. to 600° C. for approximately 1 to 8 hours. The products of the heat treatment, particularly in their metal, hydrogen, and ammonium forms, are particularly useful in the catalysis of certain organic (e.g., hydrocarbon) conversion reactions.

[0035] Any extraframework metal cations in the molecular sieve can be replaced with hydrogen, ammonium, or any desired metal cation according to techniques well known in the art (eg, by ion exchange).

[0036] Molecular sieve characterization In the as-synthesized anhydrous form, the molecular sieve SSZ-120 can have a chemical composition including the following molar relationships set forth in Table 2: [Table 2] wherein Q comprises a 3,3′-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication.

[0037] In some embodiments, the molecular sieve can have a SiO2 / GeO2 molar ratio in the range of 4 to 12 (eg, 6 to 10).

[0038] In the calcined form, the molecular sieve SSZ-120 may have a chemical composition comprising the following molar relationships: Al2O3:(n)(SiO2+GeO2) In the formula, n is ≧30 (e.g., 30 to 600, ≧60, 60 to 500, or 100 to 300).

[0039] The molecular sieve SSZ-120 has, in its as-synthesized form, an X-ray powder diffraction pattern including at least the peaks set forth in Table 3 below, and in its calcined form, the peaks set forth in Table 4. [Table 3] [Table 4]

[0040] The powder X-ray diffraction patterns presented herein were collected by standard techniques using copper K-alpha radiation. As will be appreciated by those skilled in the art, the determination of the parameter 2θ is subject to both human and mechanical errors that may combine to impose an uncertainty of approximately ±0.3° on each reported value of 2θ. Naturally, this uncertainty is also reflected in the reported values ​​of lattice spacing, which are calculated from the 2θ values ​​using Bragg's law. The relative intensity of the lines I / Io represents the ratio of the peak intensity to the intensity of the most intense line over the background. The intensities are not corrected for Lorentz and polarization effects. The relative intensities are given by the symbols VS=very strong (>60-100), S=strong (>40-60), M=medium (>20-60), and W=weak (>0-20).

[0041] Slight variations in powder X-ray diffraction patterns (e.g., experimental variations in peak ratios and peak positions) may be due to variations in atomic ratios of framework atoms due to changes in lattice constants. Additionally, sufficiently small crystals may affect peak shape and intensity, resulting in peak broadening. Calcination may cause slight shifts in the powder X-ray diffraction pattern compared to the powder X-ray diffraction pattern before calcination. Despite these slight perturbations, the crystal lattice structure may remain unchanged after calcination.

[0042] The synthesis described herein can produce molecular sieves having small crystallite sizes, such that the total surface area of ​​the material is at least 500 m 2 / g and the external surface area is at least 100 m 2 In some embodiments, the molecular sieves described herein have a molecular weight of at least 600 m 2 / g, at least 625m 2 / g, at least 650m 2 / g, e.g., 500-800m 2 / g, 600-800m 2 / g, or 650-800m 2 In addition, or alternatively, the molecular sieves described herein may comprise crystals having a total external surface area of ​​at least 100 m 2 / g, at least 110m 2 / g, at least 120m 2 / g, at least 130m 2 / g, or at least 140m 2 / g, e.g., 100-300m 2 / g, 120-300m 2 / g, or 140-300m 2 The crystals may have an external surface area of ​​1 / g. All surface area values ​​described herein are determined from the physical adsorption of nitrogen using the t-plot method. Details of this method are described by BC Lippens and JH de Boer (J. Catal. 1965, 4, 319-323).

[0043] Industrial Applicability The molecular sieve SSZ-120 (with some or all of the structure directing agent removed) may be used as an adsorbent or as a catalyst to catalyze organic compound conversion processes, including many of the processes of existing commercial / industrial importance. Examples of chemical conversion processes that are effectively catalyzed by SSZ-120, alone or in combination with one or more other catalytically active materials, including other crystalline catalysts, include processes that require catalysts with acid activity. Examples of organic conversion processes that may be catalyzed by SSZ-120 include aromatization, cracking, hydrocracking, disproportionation, alkylation, oligomerization, and isomerization.

[0044] As with many catalysts, it may be desirable to use SSZ-120 in combination with another material that is resistant to the temperatures and other conditions used in organic conversion processes. Such materials include active and inactive materials, as well as synthetic or natural zeolites, and inorganic materials, e.g., clays, silica and / or metal oxides such as alumina. The latter may be natural or in the form of gelatinous precipitates or gels including mixtures of silica and metal oxides. The use of SSZ-120 in combination with an active material (i.e., in combination with or in the presence of a new material during synthesis) tends to alter the conversion rate and / or selectivity of the catalyst in a particular organic conversion process. Inactive materials suitably function as diluents to control the amount of conversion in a given process so that products can be obtained in an economical and orderly manner without the use of other means to control the reaction rate. These materials may be incorporated into natural clays (e.g., bentonite and kaolin) to improve the crush strength of the catalyst under commercial operating conditions. These materials (i.e., clays, oxides, etc.) function as binders for the catalyst. In commercial use, it is desirable to provide a catalyst with good crush strength because it is desirable to prevent the catalyst from breaking down into powdery materials. These clay and / or oxide binders have typically been used solely to improve the crush strength of the catalyst.

[0045] Natural clays that may be formulated with SSZ-120 include the montmorillonite and kaolin families, which include sub-bentonites and kaolins commonly known as Dixie, McNamee, Georgia and Florida clays, or other clays whose major mineral components are halloysite, kaolinite, dickite, nacrite, or anaxite. Such clays may be used in the raw state as originally mined, or first calcined, acid-treated or chemically modified. Binders useful for compositing with SSZ-120 also include inorganic oxides such as silica, zirconia, titania, magnesia, beryllia, alumina, and mixtures thereof.

[0046] In addition to the materials mentioned above, SSZ-120 may be composed of porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, as well as ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.

[0047] The relative proportions of SSZ-120 and the inorganic oxide matrix can vary widely, with the SSZ-120 content ranging from 1 to 90 weight percent (eg, 2 to 80 weight percent) of the composition.

[0048] example The following illustrative examples are intended to be non-limiting.

[0049] Example 1 Synthesis of 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium]dihydroxide A 250 mL round bottom flask equipped with a magnetic stir bar was charged with 5 g of 2,6-bis(bromomethyl)naphthalene, 3.83 g of 1,2-dimethylimidazole, and 100 mL of methanol. A reflux condenser was then attached and the mixture was heated at 65° C. for 3 days. After cooling, the methanol was removed on a rotary evaporator to give a white solid. The solid initially recovered from rotary evaporation was further purified by recrystallization from cold ethanol. The recrystallized dibromide salt was: 1 H- and 13 It was found to be pure by C-NMR spectroscopy.

[0050] The dibromide salt was exchanged to the corresponding dihydroxide salt by stirring overnight with hydroxide exchange resin in deionized water, the solution was filtered and the filtrate was analyzed for hydroxide concentration by titrating a small sample with a standardized solution of 0.1 N HCl.

[0051] Example 2 Synthesis of SSZ-120 To a tared 23 mL Parr reactor, 0.27 g of Tosoh HSZ-390HUA Y-zeolite (SAR=500), 0.05 g of GeO2, and 2.5 mmol of 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium]dihydroxide in water were added. The reactor was then placed in a fume hood and the water was evaporated to a H2O / (SiO2+GeO2) molar ratio of 7 (determined by the total mass of the suspension). 2.5 mmol of HF was then added and the reactor was heated to 160°C for about 7 days while rotating at 43 rpm. The solid product was collected by centrifugation, washed with deionized water, and dried at 95°C.

[0052] Powder XRD of the as-synthesized product showed the pattern shown in Figure 1, indicating that the product was a pure form of the new phase, SSZ-120. From the peak broadening of the powder XRD pattern, it is inferred that the crystal size was significantly reduced.

[0053] Figures 2(A)-2(D) show exemplary SEM images of the as-synthesized products at various magnifications.

[0054] The product had a SiO2 / GeO2 molar ratio of 8 as determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES).

[0055] Example 3 Firing of SSZ-120 The as-synthesized molecular sieve of Example 1 was calcined in a muffle furnace under air flow heated at a rate of 1°C / min to 550°C, held at 550°C for 5 hours, cooled, and then analyzed by powder XRD.

[0056] The powder XRD pattern of the calcined material is shown in FIG. 3 and indicates that the material is stable after calcination to remove the structure directing agent.

[0057] Example 4 Example 2 was repeated using Zeolyst CBV780 Y-zeolite (SAR=80) as the FAU source. Powder XRD showed the product to be SSZ-120. Example 5

[0058] Example 2 was repeated using Zeolyst CBV760 Y-zeolite (SAR=60) as the FAU source. Powder XRD showed the product to be SSZ-120.

[0059] The product was calcined as described in Example 2. The surface area of ​​the sample was then measured using nitrogen physisorption and the data analyzed by the t-plot method. The total surface area measured was 693 m 2 / g, external surface area is 144m 2 / g. The pore volume was 0.2666 cm 3 / g.

[0060] Example 6 Example 2 was repeated using Zeolyst CBV720 Y-zeolite (SAR=30) as the FAU source. Powder XRD showed the product to be SSZ-120.

[0061] Example 7 Bronsted Acidity The Bronsted acidity of the calcined form of the molecular sieve of Example 5 was measured by n-propylamine temperature programmed desorption (TPD) adapted from the published description by TJ Gricus Kofke et al. (J. Catal. 1988, 114, 34-45); TJ Gricus Kofke et al. (J. Catal. 1989, 115, 265-272); and JG Tittensor et al. (J. Catal. 1992, 138, 714-720). The samples were pretreated at 400°C-500°C for 1 hour in flowing dry H2. The dehydrated samples were then cooled to 120°C in flowing dry helium and held at 120°C for 30 minutes in flowing helium saturated with n-propylamine for adsorption. The n-propylamine saturated sample was then heated to 500°C at 10°C / min in a dry helium stream. The Bronsted acidity was calculated based on the weight loss versus temperature by thermogravimetric analysis (TGA) and the effluent NH3 and propene by mass spectrometry. The Bronsted acidity of the sample was 250 μmol / g, indicating that aluminum sites are incorporated into the molecular sieve framework.

[0062] Example 8 Restraint Coefficient Test To measure the shape-selective catalytic behavior in molecular sieves, the constraint coefficient is tested by comparing the reaction rates of cracking n-hexane (n-C6) and its isomer 3-methylpentane (3-MP) under competitive conditions (see VJ Frillette et al., J. Catal. 1981, 67, 218-222).

[0063] The hydrogen form of the molecular sieve prepared according to Example 5 was pelletized at 4 kpsi, crushed, and granulated to 20-40 mesh. A 0.6 g sample of the granulated material was calcined in air at 540°C for 4 hours and cooled and dried in a desiccator. 0.47 g of the material was then packed into a 1 / 4 inch stainless steel tube with alundum on both sides of the molecular sieve bed. A furnace (Applied Test Systems, Inc.) was used to heat the reactor tube. Nitrogen was introduced into the reactor tube at atmospheric pressure at 9.4 mL / min. The reactor tube was heated to approximately 700°F (371°C) and a 50 / 50 feed of n-hexane and 3-methylpentane was introduced into the reactor tube at a rate of 8 μL / min. The feed was delivered by an ISCO pump. Direct sampling to the GC was started 15 minutes after the feed introduction. The results of the test data after 15 minutes on the run (700°F) are shown in Table 5. [Table 5]

[0064] Example 9 Hydroconversion of n-decane The material from Example 5 was calcined at 595°C for 5 hours in air. After calcination, 4.5 g of 0.148N NH4OH solution was mixed with 5.5 g of deionized water and then with (NH3)4Pd(NO3)2 solution (buffered at pH 9.5) at room temperature for 3 days, such that 1 g of this solution mixed with 1 g of molecular sieves provided a Pd loading of 0.5 wt%. The recovered Pd / SSZ-120 material was washed with deionized water, dried at 95°C, and then calcined at 300°C for 3 hours. The calcined Pd / SSZ-120 catalyst was then pelletized, crushed, and sieved to 20-40 mesh.

[0065] 0.5 g of Pd / SSZ-120 catalyst was loaded in the center of a 23 inch long by 1 / 4 inch outer diameter stainless steel reactor tube, and alundum was loaded upstream of the catalyst to preheat the feed (total pressure 1200 psig; downflow hydrogen rate 160 mL / min measured at 1 atm and 25°C; and downflow liquid feed rate 1 mL / hr). All materials were first reduced in flowing hydrogen at about 315°C for 1 hour. Products were analyzed every 60 minutes by on-line capillary GC. Raw data from the GC were collected by an automated data collection / processing system, and the conversion of hydrocarbons was calculated from the raw data. Conversion is defined as the amount of n-decane reacted to produce other products, including iso-C10. Yields are expressed as the mole percent of products other than n-decane, and include the iso-C10 isomer as a product. The results are shown in Figure 4 and indicate that the catalyst is highly active and not particularly selective towards isomerization, producing significant cracking products from n-decane.

Claims

1. An aluminogermanosilicate molecular sieve having, in calcined form, an X-ray powder diffraction pattern including the peaks in the following table: 【Table 4】

2. The molecular sieve has a molecular sieve adsorption capacity of at least 500 m as measured by the nitrogen physisorption t-plot method. 2 / g total surface area and / or nitrogen physisorption t-plot method 2 2. The aluminogermanosilicate molecular sieve of claim 1 comprising crystallites having an external surface area in the range of 100 / g.

3. The total surface area is 500 to 800 m 2 3. The aluminogermanosilicate molecular sieve of claim 2, wherein the molecular weight of the aluminogermanosilicate is in the range of 1:1 / g.

4. The outer surface area is 100 to 300 m 2 3. The aluminogermanosilicate molecular sieve of claim 2, wherein the molecular weight of the aluminogermanosilicate is in the range of 1:1 / g.

5. The molar relationships are as follows: Al 2 O 3 :(n)(SiO 2 +Geoem 2 ) 2. The aluminogermanosilicate molecular sieve of claim 1 having a composition having the formula:

6. An aluminogermanosilicate molecular sieve which, in its as-synthesized form, has an X-ray powder diffraction pattern containing the peaks in the following table: 【Table 3】

7. It has the following composition in molar ratio: 【Table 2A】 7. The aluminogermanosilicate molecular sieve of claim 6, wherein Q comprises 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication.

8. Having a chemical composition with the following molar relationship: 【Table 2B】 7. The aluminogermanosilicate molecular sieve of claim 6, wherein Q comprises 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication.

9. 1. A method for synthesizing an aluminogermanosilicate molecular sieve, the method comprising: (1) (a) FAU framework type zeolite; (b) a germanium source; (c) a structure directing agent (Q) comprising 3,3′-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication; (d) a source of fluoride ions; and (e) providing a reaction mixture comprising water; (2) subjecting said reaction mixture to crystallization conditions to form crystals of said aluminogermanosilicate molecular sieve.

10. 10. The method of claim 9, wherein the reaction mixture has the following composition in molar ratios: 【Table 1A】

11. 10. The method of claim 9, wherein the reaction mixture has the following composition in molar ratios: 【Table 1B】

12. 10. The method of claim 9, wherein the FAU framework type zeolite is zeolite Y.

13. 10. The method of claim 9, wherein the crystallization conditions comprise heating the reaction mixture under autogenous pressure at a temperature between 100° C. and 200° C. for a period between 1 day and 14 days.

14. 13. A process for the conversion of a feedstock containing organic compounds to a conversion product, the process comprising contacting the feedstock with a catalyst comprising the aluminogermanosilicate molecular sieve of claim 1 under organic compound conversion conditions.

Citation Information

Patent Citations

  • Synthesis method of ITQ-43 molecular sieve and ITQ-43 molecular sieve synthesized by synthesis method

    CN111099626A

  • Aluminum-substituted molecular sieve CIT-13

    JP2019534230A

  • Molecular sieve SSZ-113, its synthesis and use

    US20190256364A1